Parent-Child Communication Patterns in Digital Parenting Based on Islamic Religious Education - Wiandani, Muhammad Alfan; Rosada, Rosiana Mahari; Lukianto, Fahmi Azis; Abdussyukur, Abdussyukur (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
The development of digital technology has brought significant changes in family communication patterns, particularly between parents and children, which have impacted the process of Islamic religious education within the family. This study aims to analyze parent-child communication patterns in the digital parenting era and examine the role of family communication in fostering harmonious Islamic religious education. This study uses a qualitative approach with a literature study. Data were obtained through documentation studies from journals, books, and various relevant scientific sources, then analyzed using content analysis and qualitative descriptive techniques. The results show that the development of digital technology affects the quality of family communication, particularly the reduction in face-to-face interaction and emotional closeness between parents and children. In these conditions, digital parenting becomes an important approach that positions parents as guides, supervisors, and role models in the use of technology. Furthermore, open, compassionate communication based on Islamic values has been proven to strengthen the internalization of religious values and create family harmony. This study contributes to the development of Islamic Religious Education studies by integrating the concepts of family communication, digital parenting, and Islamic values as a relevant communication model in the digital era.